Viral protein targeting to the cortical endoplasmic reticulum is required for cell–cell spreading in plants - Wu, Chih-Hang; Lee, Shu-Chuan; Wang, Chao-Wen (The Journal of cell biology, 2011)
Many plant RNA viruses use their nonstructural proteins to target and move through the cortical endoplasmic reticulum (ER) tubules within the plant intercellular junction for cell-to-cell spreading. Most of these proteins, including the triple-gene-block 3 protein (TGBp3) of Potexvirus, are ER membrane proteins. We previously showed that TGBp3 of the Bamboo mosaic potexvirus partitions into tubular subdomains of the ER in both yeast and plants, but the mechanism and physiological significance of this localization is unclear. Here, we demonstrate that a sorting signal present in TGBp3 is necessary and sufficient for its oligomerization and for targeting integral membrane proteins into puncta within curved ER tubules. Mutations in the TGBp3 sorting signal impair viral spread, and plants infected with viruses harboring these mutants were either asymptomatic or had reduced symptoms. Thus, we propose that Potexvirus use the sorting signal in TGBp3 to target infectious viral derivatives to cortical ER tubules for transmission through the intercellular junctions in plants.